Liberation of the people - the Pathology of Power - Keppe, Norberto R. (New York Proton publishing, 1986)
This book is a deep, scientific analysis of sociopathology. It is a study of people in power and the social structure they have created, separating those who produce from those who benefit from production profits. This book introduces a practical proposal for a new model of economy and enterprises, and denounces the pathological power and corruption.